2020
DOI: 10.1111/jon.12700
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Mechanisms of Disease Progression in Multiple Sclerosis: Beyond Brain Atrophy

Abstract: Clinicians involved with different aspects of the care of persons with multiple sclerosis (MS) and scientists with expertise on clinical and imaging techniques convened in Dallas, TX, USA on February 27, 2019 at a North American Imaging in MultipleSclerosis Cooperative workshop meeting. The aim of the workshop was to discuss cardinal pathobiological mechanisms implicated in the progression of MS and novel imaging techniques, beyond brain atrophy, to unravel these pathologies. Indeed, although brain volume asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 187 publications
1
18
0
Order By: Relevance
“…The development of cognitive impairment mirrors the high individual variability that characterizes the manifestation of physical disability in MS and results from neurodegeneration [ 7 ], disconnection of salient regions [ 8 ] and functional reorganization, which, to a certain degree, is able to counteract the clinical manifestation of structural damage [ 9 ] contributing, together with intellectual enrichment [ 10 ], to cognitive reserve [ 11 ]. Conventional imaging can only give a glimpse into these complex underlying mechanisms, while the application of advanced neuroimaging techniques offers a more exhaustive picture of the different correlates of cognitive impairment [ 12 , 13 , 14 ]. In this narrative review, we provide an overview of the structural, functional and metabolic correlates of cognitive impairment in adults with MS, focusing on the more recent findings achieved via advanced neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
“…The development of cognitive impairment mirrors the high individual variability that characterizes the manifestation of physical disability in MS and results from neurodegeneration [ 7 ], disconnection of salient regions [ 8 ] and functional reorganization, which, to a certain degree, is able to counteract the clinical manifestation of structural damage [ 9 ] contributing, together with intellectual enrichment [ 10 ], to cognitive reserve [ 11 ]. Conventional imaging can only give a glimpse into these complex underlying mechanisms, while the application of advanced neuroimaging techniques offers a more exhaustive picture of the different correlates of cognitive impairment [ 12 , 13 , 14 ]. In this narrative review, we provide an overview of the structural, functional and metabolic correlates of cognitive impairment in adults with MS, focusing on the more recent findings achieved via advanced neuroimaging.…”
Section: Introductionmentioning
confidence: 99%
“…These maps are sensitive to microstructural tissue properties of high clinical relevance, such as myelin and iron content (Weiskopf et al, 2015), and have been shown to be sensitive to pathology, for example in multiple sclerosis (Jurcoane et al, 2013;Gracien et al, 2017;Lommers et al, 2019) and spinal cord injury (Grabher et al, 2015). Despite the high validity of MPM (Weiskopf et al, 2013;Leutritz et al, 2020), the widely used standard MPM protocol with 1 mm resolution (Weiskopf et al, 2013;Callaghan et al, 2014;Grabher et al, 2015;Ziegler et al, 2018;Lommers et al, 2019;Leutritz et al, 2020;Taubert et al, 2020) has a relatively long acquisition time, limiting its translational potential (Bagnato et al, 2020). Particularly in the clinical context, scan-time is minimized to increase patient comfort, reduce motion artifacts (Havsteen et al, 2017), and increase cost-efficiency for a high patient throughput.…”
Section: Introductionmentioning
confidence: 99%
“…The development of infratentorial and spinal cord lesions in the disease course is correlated with an increased risk of developing disability progression (39,44). Beyond these widely used markers, the assessments of the microglial activity, chronic permeability of the blood-brain barrier, or leptomeningeal inflammation promise a novel approach (45). Iron has been demonstrated at the rim of active macrophages and microglia in active MS lesions and could be detected with specific-weighted MRI.…”
Section: Structural Markers To Identify Ms Progressionmentioning
confidence: 99%
“…The use of positron emission tomography (PET) scans can serve as an alternative method to an in vivo evaluation of cellular activation. Alternatively, fluid-attenuated inversion recovery (FLAIR)-MRI is under evaluation for the assessment of meningeal inflammation (45). Automatized software applications, including artificial intelligence, are currently being investigated and may represent a next step in the follow-up monitoring of MS patients.…”
Section: Structural Markers To Identify Ms Progressionmentioning
confidence: 99%